Psychological impact of COVID-19 on healthcare leaders in Friuli-Venezia Giulia, Italy. (20th October 2021) - Scarpis, E; Bravo, G; Cocconi, R; Brunelli, L
Abstract: Introduction: The current pandemic scenario may cause psychological distress among healthcare workers (HCWs). Although several studies highlighted this issue as particularly affecting frontline HCWs, no data are available regarding professionals dealing with the governance of healthcare organizations. This study aims to assess the psychological impact of COVID-19 on healthcare leaders (HeLs). Methods: A cross-sectional study was carried out between October and November 2020, among HeLs working within Friuli-Venezia Giulia healthcare system (Italy). HeLs included: heads of surgical or medical department, deans of hospital, heads of doctors and nurses working at regional level or in hospital/community settings. We collected demographic data and assessed the presence of depressive (DS) and anxiety symptoms (AS), perceived stress (PS) and insomnia using internationally validated tools. Relationship between mental health outcomes and professional role was analysed using nonparametric tests. Results: A total of 48 HeLs participated; their mean age was 53.4±7.9, women were 56.3%. Most (45.8%) were heads of department, 16.7% deans of hospital, 8.3% heads of doctors, 29.2% heads of nurses. The majority (60.4%) worked in hospital setting, 22.9% in the community and 16.7% at regional level. The prevalence of DS and AS was 14.6% and 12.5%, respectively. Moderate insomnia was found in 12.5% of HeLs, while severe insomnia in 6.3% of them. The 45.8% of HeLs showed moderate level of stress, whereas 4.2% high level. PS was significantly higher among deans of hospital. Moreover, lower PS correlated with lower DS, AS and insomnia (p < 0.05). Conclusions: The high level of perceived stress, insomnia, depressive and anxious symptoms experienced by HeLs shows another issue of the COVID-19 pandemic psychological impact. Considered the key role of HeLs in leading healthcare organizations over the current crisis, mental health of these professionals is a major issue that needs higher attention. Key messages: Psychological impact of COVID19 not only affects frontline HCWs, but also the professionals who are leading healthcare organization through the crisis. Promotion of mental well-being among HCWs should be improved at all levels of healthcare organizations, ensuring a healthier workplace for all professionals working for public health.